10 years of service quality measurement: reviewing the use of the SERVQUAL instrument - Nyeck, Simon (2002)
In 1988, Parasuraman, Zeithaml, and Berry developed an instrument to measure the quality of service. Since that date, this instrument has been used in numerous studies on different industries and in different countries, both by academics and professionals. However, despite its wide dissemination, few studies deal with the dimensionality and validity aspects of this measurement scale. This article describes the practices observed in relation to these aspects through the analysis of the studies that SERVQUAL has used during the last ten years. From a sample of 60 empirical studies using the SERVQUAL scale, the main aspects of validity dealt with by each author are analysed, using an analysis template adapted from the study of Stokes and Miller (1975). Based on the available data, the study suggests that the scale developed by Parasuraman, Zeithaml, and Berry (1988) does not present a stable dimensional structure of five factors. Finally, the article evaluates the influence of the characteristics of the research design on the reliability of SERVQUAL.